Reversal of multidrug resistance by cisplatin-loaded magnetic Fe3O4 nanoparticles in A549/DDP lung cancer cells in vitro and in vivo - Li K (Dove Medical Press, 2013)
Ke Li,1 Baoan Chen,1,2 Lin Xu,3 Jifeng Feng,3 Guohua Xia,1,2 Jian Cheng,1,2 Jun Wang,1,2 Feng Gao,1,2 Xuemei Wang,41Department of Hematology, Key Medical Disciplines of Jiangsu Province, Zhongda Hospital, Medical School, Southeast University, Nanjing, 2Faculty of Oncology, Medical School, Southeast University, Nanjing, 3Department of Thoracic Surgery, Jiangsu Province Cancer Hospital, Jiangsu Province, 4State Key Laboratory of Bioelectronics, Southeast University, Nanjing, People’s Republic of ChinaAbstract: The purpose of this study was to explore whether magnetic Fe3O4 nanoparticles (Fe3O4-MNP) loaded with cisplatin (Fe3O4-MNP-DDP) can reverse DDP resistance in lung cancer cells and to investigate mechanisms of multidrug resistance in vitro and in vivo. MTT assay showed that DDP inhibited both A549 cells and DDP-resistant A549 cells in a time-dependent and dose-dependent manner, and that this inhibition was enhanced by Fe3O4-MNP. An increased rate of apoptosis was detected in the Fe3O4-MNP-DDP group compared with a control group and the Fe3O4-MNP group by flow cytometry, and typical morphologic features of apoptosis were confirmed by confocal microscopy. Accumulation of intracellular DDP in the Fe3O4-MNP-DDP group was greater than that in the DDP group by inductively coupled plasma mass spectrometry. Further, lower levels of multidrug resistance-associated protein-1, lung resistance-related protein, Akt, and Bad, and higher levels of caspase-3 genes and proteins, were demonstrated by reverse transcriptase polymerase chain reaction and Western blotting in the presence of Fe3O4-MNP-DDP. We also demonstrated that Fe3O4-MNP enhanced the effect of DDP on tumor growth in BALB/c nude mice bearing DDP-resistant human A549 xenografts by decreasing localization of lung resistance-related protein and Ki-67 immunoreactivity in cells. There were no apparent signs of toxicity in the animals. Overall, these findings suggest potential clinical application of Fe3O4-MNP-DDP to increase cytotoxicity in lung tumor xenografts.Keywords: Fe3O4, nanoparticles, multidrug resistance, reversal, DDP-resistant A549 cells, cisplatin